2021
DOI: 10.3390/molecules26247424
|View full text |Cite
|
Sign up to set email alerts
|

Scientifically Formulated Avocado Fruit Juice: Phytochemical Analysis, Assessment of Its Antioxidant Potential and Consumer Perception

Abstract: The study’s purpose was to find and create a nourishing fruit juice made from avocado to suit nutritional and health demands. In this regard, the avocado juice was formulated using a statistical technique, and its biochemical and phytochemical characteristics were evaluated. Statistically formulated fruit juice was evaluated for its sensory characteristics, proximate composition, nutrients and vitamins, total phenols and flavonoids, and for its antioxidant ability, in addition to a shelf-life test. The optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Color, flavor, taste, and acceptability also showed weak or no correlation with pH, RS, total sugars, TPC, and antioxidants. The use of heat maps for quality assessment and optimization of juice generation from fruit samples has been previously well reported. ,, In a previous study, Zhang et al . generated a heat map through Pearson correlation analysis to comprehensively assess fruit quality and identify aroma-active compounds in green pepper.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Color, flavor, taste, and acceptability also showed weak or no correlation with pH, RS, total sugars, TPC, and antioxidants. The use of heat maps for quality assessment and optimization of juice generation from fruit samples has been previously well reported. ,, In a previous study, Zhang et al . generated a heat map through Pearson correlation analysis to comprehensively assess fruit quality and identify aroma-active compounds in green pepper.…”
Section: Resultsmentioning
confidence: 99%
“…The use of heat maps for quality assessment and optimization of juice generation from fruit samples has been previously well reported. 37,66,67 In a previous study, Zhang et al 67 generated a heat map through Pearson correlation analysis to comprehensively assess fruit quality and identify aroma-active compounds in green pepper. Their research findings elucidated the primary texture-related attributes of pepper and identified the key aroma-active compounds, thereby offering valuable insights for improving pepper quality through breeding programs and establishing consumer guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation